Tripodal triptycenes as a versatile building block for highly ordered molecular films and self-assembled monolayers - Zharnikov, Michael; Shoji, Yoshiaki; Fukushima, Takanori (Accounts of chemical research, 2025)
ConspectusThe design of properties and functions of molecular assemblies requires not only a proper choice of building blocks but also control over their packing arrangements. A highly versatile unit in this context is a particular type of triptycene with substituents at the 1,8,13-positions, called tripodal triptycene, which offers predictable molecular packing and multiple functionalization sites, both at the opposite 4,5,16- or 10 (bridgehead)-positions. These triptycene building blocks are capable of two-dimensional (2D) nested hexagonal packing, leading to the formation of 2D sheets, which undergo one-dimensional (1D) stacking into well-defined “2D+1D” structures. This ability makes it possible to form large-area molecular films having long-range structural integrity even on polymer substrates, which can be used to enhance the performance of organic devices. Importantly, the 2D assembly ability of tripodal triptycenes is robust and not impaired when chemically modified with functional molecular units and even with polymer chains. In addition, introducing suitable functionalities that act as anchoring groups results in reliable tripodal monomolecular assembly on application-relevant inorganic substrates, which is generally considered quite a challenging task. Self-assembled monolayers (SAMs) have been formed on Au(111), Ag(111), and indium tin oxide. On gold, these SAMs feature the nested hexagonal packing typical of 2D triptycene sheets, whereas, on silver, a distinct polymorphism with several different packing motifs occurs. Along with basic, nonsubstituted tripodal SAMs, specifically functionalized monolayers have been designed. A substitution pattern in which three nitrile tail groups build the outermost surface of a tripodal triptycene-based SAM has allowed for the study of femtosecond charge transfer dynamics across the triptycene framework, with a particular emphasis on the so-called matrix effects involving intramolecular pathways. The functionalization of the bridgehead position with a ferrocene tail group has enabled single-molecule observation of redox reactions and the creation of assemblies of unique molecular rectifiers, exhibiting highly effective rectification at a very low bias voltage. Complementary to the synthesis of these complex functional triptycenes, a strategy of on-surface click reactions has been designed. Indeed, a tripodal triptycene having an ethynyl tail group at the 10-position, capable of click reactions with azide functionalities, works well, allowing successive molecular layer deposition. The performance of tripodal triptycene-based SAMs has also been tested in the context of electron beam lithography (EBL) and nanofabrication, leading to the finding that these SAMs can serve as negative resists for EBL due to the efficient cross-linking, giving rise to triptycene-stemming carbon nanomembranes (CNM). These membranes feature the lowest lateral material densities used to date for CNM preparation, which makes them unique in this regard.